Clinical cardiac manifestations in patients with coronavirus disease 2019 (COVID-19) - Hafizha Herman; Putrika PR Gharini; Lucia Kris Dinarti (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
The pandemic of coronavirus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has infected more than 2 million people worldwide with case fatality rates between 3-15%. The pathophysiology of this newly emerging disease in affecting cardiovascular system is poorly understood. This review aimed to understand from various retrospective studies and case reports that have been published and updated during the pandemic of COVID-19 related to the underlying mechanism and cardiovascular interaction with coronavirus. A literature search was done with Google search, PubMed, European Society of Cardiology (ESC) and Journal of American Medical Association (JAMA) network since the early days of COVID-19 pandemic. Clinical presentation may be asymptomatic or the severe cases will have acute respiratory distress syndrome (ARDS). Protein spikes of SARS-CoV-2 virus use the angiotensin-converting enzyme 2 (ACE2) as viral entry to host cells. Due to the upregulation of ACE2, people with any pre-existing cardiac diseases are more vulnerable to the infection and more likely to have a severe condition of COVID-19 infection with a higher risk of mortality. On the other hand, ACE2 has protective effects against myocardial inflammation and lung injuries. Several cases of COVID-19 infection may have cardiac manifestations as a chief complaint or acute cardiac injury as the complication. Recent case reports show that acute cardiac injury, myocarditis, cardiogenic shock, thromboembolism, and arrhythmias could be the complications of COVID-19 even without history or risk factors of cardiovascular disease. There are several hypotheses related to the mechanism of acute cardiac injury in COVID-19 patients, including damage through ACE2 receptors, hypoxia, cardiac microvascular damage, and inflammatory response.COVID-19 infection can cause many interactions in the cardiovascular system, whether the patients already had chronic heart disease or not. Considering the lack of evidence of the RAS inhibitor in COVID-19, the use of ACE inhibitor/ARB should be continued unless contraindicated and may be beneficial in patients with hypertension, heart failure and diabetes mellitus. Early recognition of cardiac manifestations from COVID-19 infections will be the key to prevent short and long term cardiac adverse events.